The Impact of Russia's Invasion on European Attitudes - Margaryta Klymak; Tim Vlandas (London School of Economics and Political Science (LSE), European Institute, 2023)
What is the effect of wars abroad on the attitudes of people living in countries that are not directly involved? Using the tenth wave of the European Social Survey, this paper explores how the Russian invasion has affected the political and social attitudes of people across eight European countries. The overlap between the survey fieldwork in these eight countries and the Russian invasion allows us to recover causal estimates by adopting the 'Unexpected Event during Survey Design'. We find that the invasion increased support for democracy and the welfare state, reinforced positive views of the European Union and immigration, while it reduced authoritarian attitudes.
Keywords: 330; Attitudes; unexpected event during survey design; Russia’ s invasion; European Social Survey; immigration attitudes; democracy; authoritarianism; redistribution; EU; war; conflict